A Study of Avoidance Strategy of Face Threat of Native Speaker and Non-Native Speaker by Using Goffman’s Face-Work Theory - Salmon Pandarangga (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2015)
The purpose of this study was to analyze the avoidance strategy of face threat by English native speaker and non-native speaker who learnt other language e.g. English. This study used Irving Goffman’s face-work theory and its relation to avoidance face threat as a framework. 2 participants (one Australian and one Indonesian) took part in this study. Both participants were interviewed in English language in English speaking environment for about 30 minutes each. The participants were asked to tell about their hobbies with some open-ended questions. This study focused on spoken sentences produced by both interviewees that indicated avoidance of face threat. The findings revealed that the native speaker and non-native speaker reacted differently to avoid face threat. In addition, they also had their own strategy to avoid the face threat. This study concluded that different cultures significantly contributed to the strategy of avoidance of face threat. Permalink/DOI: http://dx.doi.org/10.15408/ijee.v2i2.3087